Training of facilitators in problem-based learning: a Malaysian experience - Othman, Hussain (2013)
Training of facilitators in Problem-Based Learning (PBL) is one of the most challenging tasks facing by higher learning institutions in Malaysia. It was time consuming and demanded high level of commitment from university leaders and training facilitators to prepare and equip the academics with proper skills in PBL. A number of institutions have taken their pro active efforts to train their academics in PBL through organized training sessions internally or externally. Unfortunately, some training sessions were unable to prepare and equip the academics with knowledge and skills to run a proper PBL at their respective institutions. In order to improve this situation, a group of PBL practitioners from three public universities are working together to develop a proper training module to train academics in PBL. The module was initially developed in 2010 and since then was applied in seven training sessions until end of 2012. A questionnaire set was developed in order to identify the effectiveness of this module based on 3C3R Model developed by Hung (2006). Findings show that the module has met six 3C3R standards, i.e. (1) having appropriate content related to PBL, (2) the problems are connected closely to the content and (3) the context of learning. Activities (4) required the participants to research, (5) reason and (6) reflect. The participants highly regarded the module and satisfied with the skills of using PBL and active learning experiences during the workshops.